Implementation of Problem-Based Learning Using the Quizizz Application to Increase Students’Interest in Learning - Supriyanto; Syamsuri (Postgraduate, University of Mataram, 2025)
This study examines the impact of implementing Problem-Based Learning (PBL) with the Quizizz application on students' interest in learning citizenship education for Class X at SMA Negeri 1 Tanjung Palas Tengah during the 2024–2025 academic year. Conducted as Classroom Action Research (CAR) over two cycles, the study follows the stages of planning, implementation, observation, and reflection. Data were collected through observations, questionnaires, and assessments. The findings indicate a significant increase in students' learning interest, as evidenced by a 25% improvement in questionnaire scores measuring engagement and motivation, alongside an increase in daily assessment scores from an average of 70 in the first cycle to 85 in the second cycle. Students exhibited greater enthusiasm, active participation, and positive responses toward the learning process. These results suggest that integrating PBL with the Quizizz application effectively enhances student engagement and motivation in citizenship education. The study highlights the potential of interactive digital tools to support innovative teaching strategies and improve learning outcomes.